Rancang Bangun Sistem Monitoring Suhu Pasien Rawat Inap Berbasis Internet of Things - Dedi Suarna (Management of Information System Journal, 2026)
Monitoring the health condition of inpatients is an important aspect of hospital services to ensure optimal patient monitoring. The manual process of monitoring body temperature has several obstacles, such as limited time for medical personnel, delays in obtaining information on patient conditions, and the ineffectiveness of the continuous monitoring process. This study aims to design and build an Internet of Things (IoT)-based inpatient body temperature monitoring system that is capable of providing real-time patient condition information. This system uses a DS18B20 temperature sensor as a patient temperature reader and a NodeMCU ESP8266 as a microcontroller that functions to process and transmit data via the internet. The temperature data obtained is displayed on the Blynk application on a smartphone so that it can be monitored by medical personnel anytime and anywhere. The research methods used include observation, interviews, literature studies, system design, hardware and software implementation, and system testing. The results of the study indicate that the system built is able to read patient body temperature well, send data to the Blynk server, and display temperature information in real-time on a smartphone device. Thus, this IoT-based patient health monitoring system can assist medical personnel in monitoring patient conditions more effectively, quickly, and efficiently.